2006
DOI: 10.2987/8756-971x(2006)22[149:caaoof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cold Acclimation and Overwintering of Female Aedes Albopictus in Roma

Abstract: Eight years after the introduction and establishment of Aedes albopictus in Roma, females of the species extended their trophic activity to the coldest months of the year. Winter monitoring carried out from December 2003 to March 2004 in the urban area of the capital city of Italy recorded a weekly rate of positive ovitraps constantly around 30%, for the entire period of surveillance (14 wk). Eggs from ovitraps did not hatch when stimulated in laboratory with a wet and dry procedure. The hypothesis that long-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 1 publication
0
72
0
2
Order By: Relevance
“…The production of eggs that enter diapause (stimulated by changes in photoperiod), which withstand cold winter temperatures (Hawley 1988;Medlock et al 2006), as well as cold acclimation of adult females (Romi et al 2006), have facilitated its spread in northern states in the U.S. (Hawley, 1988), and will permit its survival in parts of northern Europe. Specific mapping and modeling of the most likely areas for establishment of A. albopictus in Europe, and the potential spread with climate change is available from the ECDC (2009).…”
Section: Biotic and Abiotic Factors Constraining Establishment In Europementioning
confidence: 99%
“…The production of eggs that enter diapause (stimulated by changes in photoperiod), which withstand cold winter temperatures (Hawley 1988;Medlock et al 2006), as well as cold acclimation of adult females (Romi et al 2006), have facilitated its spread in northern states in the U.S. (Hawley, 1988), and will permit its survival in parts of northern Europe. Specific mapping and modeling of the most likely areas for establishment of A. albopictus in Europe, and the potential spread with climate change is available from the ECDC (2009).…”
Section: Biotic and Abiotic Factors Constraining Establishment In Europementioning
confidence: 99%
“…In addition, the detection of WNV in pools of overwintering hibernating Culex pipiens mosquitoes in New York City in 2000 [74] clearly indicates the capacity of the virus to overwinter and to survive in hibernating infected adult mosquitoes. The survival of adult mosquitoes during winter and even a certain level of adult activity were sometimes observed in the Mediterranean countries and in other temperate areas [75-77]. …”
Section: Outbreaks Caused By Lineage 1 Wnd Strainsmentioning
confidence: 99%
“…Giatropoulos et al (2012) found that the numbers of the produced eggs are the highest in mid-July to November. Romi et al (2006) proved that Ae. albopictus can adapt for the local environment which means that natural selection results strains with different climatic requirements and overwintering potential.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus populations (Thomas et al, 2012). In addition, in the Mediterranean, as the coastal and lowland areas of the Apennine Peninsula where the more severe freeze is rarely occur, the populations of the Asian tiger mosquito shows the signs of cold-acclimation as adults and remain active throughout the entire winter season (Romi et al, 2006). Larval development including each of the instars takes 3-8 weeks, while the mean lifespan of the adults is about 3 weeks, although in case of the overwintering individuals of female mosquitoes in the Mediterranean area it can takes some months (Gatt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%